2016
DOI: 10.1097/pec.0000000000000537
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Suicide Risk Among Pediatric Emergency Department Patients

Abstract: Objectives To describe the association between recent bullying victimization and risk of suicide among pediatric emergency department (ED) patients. Methods Patients presenting to one of three different urban pediatric EDs with either medical/surgical or psychiatric chief complaints completed structured interviews as part of a study to develop a suicide risk screening instrument, the Ask Suicide-Screening Questions (ASQ). Seventeen candidate items and the criterion reference Suicidal Ideation Questionnaire (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
(30 reference statements)
1
13
0
3
Order By: Relevance
“…Consistent with recent media coverage, a history of being bullied also confers a dynamic risk factor for the child/adolescent age group. The victims of bullying as well as the bullies themselves are both at increased risk for suicide . Some studies have found that children who are both victims and bullies are at higher risk for suicide attempts than being victims or bullies alone .…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with recent media coverage, a history of being bullied also confers a dynamic risk factor for the child/adolescent age group. The victims of bullying as well as the bullies themselves are both at increased risk for suicide . Some studies have found that children who are both victims and bullies are at higher risk for suicide attempts than being victims or bullies alone .…”
Section: Resultsmentioning
confidence: 99%
“…Trends Several reasons have been suggested for the growing increase in depression, SI and SA, and suicide among children and adolescents. Bullying 34,35 (particularly the rise of social media and cyberbullying 36,37 ), the decreasing age of puberty in girls, 38,39 and trends in the use of antidepressants 40 have been proposed as possible factors. The effect of the economic crisis of 2008 has also been examined, although its effect on adolescent suicide-related behavior remains less understood than adult behavior.…”
Section: Figurementioning
confidence: 99%
“…In general, the negative consequences for the victims include a sense of insecurity, loneliness, decreased self-esteem, insomnia, depression, school absenteeism, low academic performance, and suicidal ideation, among other consequences. [8][9][10] Victims are generally described as being socially isolated, which restricts the amount of support and help they receive from peers, while at the same time, they do not have the social skills necessary to ask for help from their peers or adults. [11][12] Hence, victimization may occur for long periods without being noticed and more severely impact the education and health of students in the medium or long terms.…”
Section: Introductionmentioning
confidence: 99%